RELATIONSHIP OF ONLINE LEARNING WITH MOTHER'S STRESS LEVEL IN ACCOMPANYING CHILDREN TO STUDY FROM HOME DURING THE COVID-19 PANDEMIC - VERI VERI; HOLIDAH HOLIDAH; SAFITRI RAHAYU (NURSING ANALYSIS: Journal of Nursing Research, 2022)
ABSTRACTCovid-19 has had an impact on various sectors, including the education sector. In an effort to prevent the spread and minimize the possibility of contracting Covid-19, the government through the Ministry of Education and Culture has implemented an online learning policy. Theoretically, online learning provides easy access to information in the educational process, but in practice there are various obstacles faced by mothers as children's companions at home, this results in high levels of stress on mothers. The purpose of this study was to determine the relationship between online learning and the mother's stress level in accompanying children to study from home during the Covid-19 pandemic at Public Elementary School Puspiptek South Tangerang. This research method uses a quantitative design with a cross sectional. The research population was 119 respondents with total sample of 74 respondents who were obtained by method probability sampling, namely technique proportionate stratified random sampling. Data were analyzed using chi square. The results obtained from 74 respondents, 59 respondents (79.7%) conducted online learning regularly and 15 respondents (20.3%) conducted online learning irregularly. From 74 respondents, 35 respondents (47.3%) experienced severe stress, 30 respondents (40.5%) experienced moderate stress and 9 respondents (12.2%) experienced mild stress. The results of statistical test obtained a value (p-value = 0,00, α  = 0,05), it can be concluded that there is a relationship between online learning and the stress level of mothers in accompanying children to study from home during the Covid-19 pandemic at Public Elementary School Puspiptek South Tangerang. Suggestions after the research is expected that the results of this study can be used as information in providing nursing care to clients related to therapy to reduce stress levels.                                                                                                      Keywords: Covid-19 Pandemic, Online Learning, Stress Level HUBUNGAN PEMBELAJARAN DARING DENGAN TINGKAT  STRES IBU DALAM MENDAMPINGI ANAK BELAJAR DARI RUMAH SELAMA PANDEMI COVID-19  ABSTRAKCovid-19 memberikan dampak pada berbagai sektor, tidak terkecuali sektor pendidikan. Dalam upaya mencegah penyebaran dan meminimalkan kemungkinan tertularnya Covid-19, pemerintah melalui Kemendikbud menerapkan kebijakan pembelajaran daring.  Secara teoritis, pembelajaran daring memberikan kemudahan akses informasi dalam proses pendidikan, namun pada praktiknya dijumpai berbagai kendala yang dihadapi ibu  sebagai pendamping anak dirumah, hal ini mengakibatkan tingginya tingkat stres pada ibu. Tujuan penelitian ini adalah untuk mengetahui hubungan pembelajaran daring dengan tingkat stres ibu dalam mendampingi anak belajar dari rumah selama pandemi Covid-19 di SDN Puspiptek Tangerang Selatan. Metode penelitian ini menggunakan desain kuantitatif dengan pendekatan cross sectional. Populasi penelitian berjumlah 119 responden dengan jumlah sampel sebanyak 74 responden yang didapatkan dengan metode probability sampling yaitu teknik proportionate stratified random sampling. Data dianalisis menggunakan uji chi square. Hasil penelitian diperoleh dari 74 responden sebanyak 59 responden (79,7%) melakukan pembelajaran daring secara teratur dan sebanyak 15 responden (20,3%) melakukan pembelajaran daring secara tidak teratur. Dari 74 responden, sebanyak 35 responden (47,3%) mengalami stres berat, 30 responden (40,5%) mengalami stres sedang dan 9 responden (12,2%) mengalami stres ringan. Hasil uji statistik didapatkan nilai (p-value = 0,00, α  = 0,05) maka dapat disimpulkan bahwa ada hubungan pembelajaran daring dengan tingkat stres ibu dalam mendampingi anak belajar dari rumah selama pandemi Covid-19 di SDN Puspiptek Tangerang Selatan. Saran setelah dilakukan penelitian diharapkan hasil penelitian ini dapat dijadikan informasi dalam memberikan asuhan keperawatan kepada klien terkait terapi untuk mengurangi tingkat stres.                                                                                           Kata kunci : Pandemi Covid-19, Pembelajaran Daring, Tingkat Stres